Change and Transformation of Functions in Turkey’s Felt Objects - Tarcan, Berilsu (FormAkademisk, 2023)
This study analyses felt and the practice of felting from the geography of Turkey, as a way to explore felt’s function in material culture. Felting is a method of craft making that consists of compressing fibres (wool or other). Felt, (in Turkish “keçe”) can be defined as the outcome product of felting process. However, keçe represents more than just a cloth or a textile. It was an important part of daily life in the geography of Turkey, for instance among nomads who produced their daily necessities from felt. For the study, first, I introduce some felt products from Turkey. Afterwards, I share the processes and results of a field study, through observations and interviews conducted with feltmakers in Tire region in Turkey. Then I share an analysis and results from the product research and field study. Nowadays felt is found through another range of accessories and artistic works, such as decorational products, hair bands, slippers, vase, tumbler, hats. While felt was commonly used for important functions such as carrying, moving; today, other materials are used for these functions. Therefore, felt objects can be perceived and bought as accessories rather than necessities in modern culture. Nevertheless, felt is still used for the representation of identities. Although felt is considered to have lost its value, for the context of Turkey, I argue that the functions have shifted to new contexts. Through different functionalities such as being tools for self-expressions/communication, felt has a similar value in the current culture.